Venoarterial Membrane Oxygenation in Cardiogenic Shock Complicated from an Acute Myocardial Infarction: An Overview and Comprehensive Meta-Analysis - Kiarash Sassani; Styliani Syntila; Christian Waechter; Julian Kreutz; Birgit Markus; Nikolaos Patsalis; Bernhard Schieffer; Georgios Chatzis (Biomedicines)
Background: Cardiogenic shock remains a significant cause of mortality in patients with acute coronary syndrome, despite early interventions, such as coronary revascularization. Mechanical circulatory support devices, particularly venoarterial extracorporeal membrane oxygenation (VA-ECMO), are increasingly being utilized to address this issue. Limited randomized controlled trials (RCTs) exist to evaluate the efficacy of VA-ECMO in cardiogenic shock related to acute coronary syndrome. Methods: A meta-analysis was conducted to assess the effectiveness of VA-ECMO in adult patients with infarct-related cardiogenic shock. Trials were identified through database searches and selected based on specific inclusion criteria. The primary outcome was 30-day all-cause mortality, with secondary outcomes including bleeding and vascular complications. Results: A total of 24 studies met the inclusion criteria and were included in the meta-analysis, involving 4706 patients. The median age of the patients was 61.8 ± 4.1 years, with 76% of them being males. The analysis revealed that 30-day mortality rates for patients with cardiogenic shock receiving ECMO were still high, with a mortality of 63%. Vascular complications were identified as factors associated with a worse prognosis. Conclusions: The meta-analysis highlights the ongoing challenge of high mortality rates in cardiogenic shock patients despite the use of VA-ECMO. While VA-ECMO shows promise in providing circulatory support, further research is needed to explore ways to improve outcomes and reduce complications associated with the use of these devices. The complexity of patient management in cardiogenic shock cases underscores the need for a multidisciplinary approach to optimize treatment strategies and enhance patient outcomes.